Pathology of the appendix - Williams, Richard A; Myers, Paul (Chapman and Hall, 1994)
Diseases of the appendix are common, and it is the organ most commonly removed during surgery. Over 60,000 appendectomies are carried out annually in the United Kingdom. This is partly due to the difficulty of locating the precise source of abdominal pain and to the potential complications of acute appendicitis. Another factor is that the symptoms and signs of appendicitis are often hard to distinguish from other causes. These difficulties lead to many \"normal\" appendices being removed unnecessarily. A better understanding of the pathology of the appendix might prevent some of this inappropriate surgery. This book is a ready reference bench guide for pathologists and surgeons. It is illustrated with extensive supporting text and references. This book should be of interest to pathologists, general and abdominal surgeons.
Keywords: nádory apendixu; Appendicitis; Appendiceal Neoplasms; gastroenterologie; Appendix; apendix; apendicitida